-3(-7u+8)-3u=6(u-1)-8

Simple and best practice solution for -3(-7u+8)-3u=6(u-1)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-7u+8)-3u=6(u-1)-8 equation:



-3(-7u+8)-3u=6(u-1)-8
We move all terms to the left:
-3(-7u+8)-3u-(6(u-1)-8)=0
We add all the numbers together, and all the variables
-3u-3(-7u+8)-(6(u-1)-8)=0
We multiply parentheses
-3u+21u-(6(u-1)-8)-24=0
We calculate terms in parentheses: -(6(u-1)-8), so:
6(u-1)-8
We multiply parentheses
6u-6-8
We add all the numbers together, and all the variables
6u-14
Back to the equation:
-(6u-14)
We add all the numbers together, and all the variables
18u-(6u-14)-24=0
We get rid of parentheses
18u-6u+14-24=0
We add all the numbers together, and all the variables
12u-10=0
We move all terms containing u to the left, all other terms to the right
12u=10
u=10/12
u=5/6

See similar equations:

| -n+5n-4+7=19 | | .17x(50000-x)=6000 | | 8-2d=-18d+12+19d | | 1-3x=5-2 | | 4(4x+3)=21x+11-5x+1 | | -12+42=-3(x+5) | | 1/5(x+5)=4 | | 9r+2=7(r-5)÷3 | | 13x+20-9x=32 | | 3x+28=-x-4 | | 29=6+10+x | | x+25=3x–25 | | z+9z=81-4 | | q/4−1=3 | | (5x+1)/((x^2-2x)+3/(2-X)=1/(4x) | | 8(2-x)/7=-x | | 5(n2+n)=3(n2-2n) | | 4d-2d÷3=10 | | 21=|x-20| | | -f+2+4f=8-4f | | -4y=15-3y | | 11x-1=2x+43 | | 3+9=-2(2x-6) | | 2x-4x+3=-13 | | q4−1=3 | | 4w-7=2w+13=-26 | | 9d-3d=24 | | 29=6+10=x | | 24x+7=25x+3 | | 8(9x+7)=-15 | | 5(x-3)=3+-12 | | 8.4-15.3y=-17.12-19.8y-5.53 |

Equations solver categories